Reception of Eucharist by Alzheimer's patient: Canons 913 and 914 - Kaslyn, Robert J. (Roman replies and CLSA advisory opinions 1995, 1995)
My mother, Mrs. Jones, a devout Catholic all her life, is suffering from Alzheimer’s disease and is confined to a nursing home. The disease has progressed to the point that she does not recognize all family members when they visit; however, she is able to eat food without regurgitation. Recently, Fr. Justin, the chaplain at the diocesan nursing home and a priest for fifty-five years, has refused to give Holy Communion to my mother, stating that she has lost the use of reason. Before seeking canonical advice, I first attempted to discuss the issue with the Bishop of Antioch. He refused to review the case and appeared unwilling to reverse the decision of Fr. Justin. I then wrote to the bishop, respectfully requesting that he provide a written decree explaining the reasons for his decision and further requesting that he either revoke or amend his decision and inform Fr. Justin that he should give Holy Communion to my mother. In response, the bishop developed an argument based on the Code of Canon Law. He referred to the necessity of the use of reason for the reception of Holy Communion and raised the question of whether Mrs. Jones is properly disposed to receive the Eucharist. The pertinent portions of his response are as follows: “Fr. Justin has determined that Mrs. Jones does not demonstrate the use of reason, does not exhibit signs of recognition of the Eucharist, and does not display an ability to distinguish between the Eucharist and other food and medicine which she receives. I have also asked Father Augustine, the local pastor, to visit your mother. He did so and reported that Mrs. Jones demonstrated very little awareness of his presence. She did not appear to understand that he was a priest. She did not know what Holy Communion was. She was not able to join him in prayer. His opinion is that he does not consider it appropriate to give Holy Communion to Mrs. Jones.” The bishop concluded, “Unless some evidence can be presented which demonstrates that Mrs. Jones has the use of reason, I must support the considered and prayerful decision of the chaplain of the nursing home.” Given this response from the Bishop of Antioch, what can I do now to have my mother receive the Eucharist?